Cytokine-stimulated secretion of group II phospholipase A2 by rat mesangial cells. Its contribution to arachidonic acid release and prostaglandin synthesis by cultured rat glomerular cells. - Pfeilschifter, J (1993)
Potent pro-inflammatory cytokines, such as interleukin 1 (IL-1) or tumor necrosis factor (TNF) alpha have been found to increase group II phospholipase A2 (PLA2) synthesis and secretion by mesangial cells. In all cases 85-90% of the enzyme is secreted from the cells and a parallel increase in prostaglandin (PG)E2 synthesis is observed. We report here that co-incubation with a monoclonal antibody that specifically binds and neutralizes rat group II PLA2 attenuates IL-1 beta and TNF alpha-stimulated PGE2 production by 45% and 52%, respectively. CGP43182, a specific inhibitor of group II PLA2, potently blocks mesangial cell group II PLA2 in vitro with a half-maximal inhibitory concentration (IC50) of 1.5 microM, while only slightly affecting mesangial cell high molecular weight PLA2. CGP 43182 markedly attenuates IL-1 beta- and TNF alpha-stimulated PGE2 synthesis in intact mesangial cells with IC50's of 1.3 and 1.0 microM, respectively. PLA2 secreted from cytokine-stimulated mesangial cells was purified to homogeneity. Addition of the purified enzyme to unstimulated mesangial cells causes a marked release of arachidonic acid and a subsequent increased synthesis of PGE2. Moreover, addition of purified PLA2 to a cloned rat glomerular epithelial cell line and cultured bovine glomerular endothelial cells augmented both arachidonic acid release and PGE2 synthesis, with the endothelial cells being especially sensitive. Thus, cytokine-triggered synthesis and secretion of group II PLA2 by mesangial cells contributes, at least in part, to the observed synthesis of PGE2 that occurs in parallel to the enzyme secretion. Furthermore, extracellular PLA2 secreted by mesangial cells is able to stimulate arachidonic acid release and PGE2 synthesis by the adjacent endothelial and epithelial cells. These data suggest that expression and secretion of group II PLA2 triggered by pro-inflammatory cytokines may crucially participate in the pathogenesis of inflammatory processes within the glomerulus.